VALUE ENGINEERING OF TOP STRUCTURE WORKS TO INCREASE BUDGET EFFICIENCY IN THE MALANG TRANSMART DEVELOPMENT PROJECT - Edi Santoso, Rizki Amalia Dambayanti (Universitas Negeri Malang, 2021)
Abstract:Value engineering is a creative approach that is systematically organized in analyzing the function of an item in order to be able to optimize costs by reviewing project stages and eliminating unnecessary costs. By applying value engineering, it is expected to produce lower cost alternatives without reducing the quality that has been determined. This study aims to determine the alternative design of efficient work methods, safety control on the design structure, and cost savings in the construction project of the Transmart Malang building. The value engineering analysis applied in this research includes the information stage, the speculation stage, the analysis stage, the development stage, and the final recommendation presentation stage. The analysis carried out on the Transmart Malang building construction project resulted in the work of the superstructure having a large enough cost, therefore it is necessary to do an alternative design and calculation of cost efficiency. After analyzing the Transmart Malang building construction project, it was found that the largest costs were on the work of columns, beams, and floor slabs. In column work, an alternative is the use of the fabrication precast column method with savings ofRp 304,040,832.00 or 3.431%from the initial design. In beam work, an alternative is the use of the precast beam fabrication method with savings ofRp 994.312.116.00 or 7.757%from the initial design. While on the floor slab work, an alternative is the use of the half slab slab method with a savings of Rp. 794,344,675.00 or 2,055% from the initial design. So that in the final analysis, the results of the savings on all structural work are Rp. 2,092,697,624.00 or 3.119% of the initial design.Keywords: Value Engineering, Floor Plates, , Beams, Columns, Cost Savings